Morpho-Syntactic Errors in EFL Students’ Writing: A Lesson from Language Education Institutions - Fajrin, Zainul; Manurung, Konder; Bochari, Siska; Hastini, Hastini; Hassan, Ahmad Javed (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Many students struggle with writing in English due to linguistic challenges such as morphology and syntax. This research aimed at discovering the morpho-syntactic errors that EFL students did and the most dominant error in the fifth-semester students in the English Education Study Program at Tadulako University. The researcher used descriptive quantitative method as the design of the research to analyze common morpho-syntactic error in on the students’ writings and to discover the errors and the most dominant errors made by students. The participants of this research were 145 students which chosen using simple random sampling where the researcher picked sample members from a population at random, without worrying about different groups or layers within that population. Data for this study were gathered through tests and the researcher analyzed using Dulay’s linguistic category taxonomy. The results of the study showed that errors are found at both morphological and syntactical levels. The morphological level included pronoun error, quantifier error, and inflectional error. Meanwhile, the syntactical level included tense error, infinitive error, auxiliary verb error and subject-verb agreement error. However, from all those errors, the most dominant error was pronoun error with the total number of errors was 504 in frequency. It implied that students lacked of understanding the use of pronouns in sentences. The research findings have important implications for both pedagogical approach and linguistic competence. For pedagogical approach, the insights help students understand and correct common grammar errors, improving their writing skills and boosting their confidence. In terms of linguistic competence, the findings highlight EFL students' development in morphology and syntax, enabling them to construct grammatically correct sentences and master complex language structures.